Infracțiunea de ultraj în spațiul european - Năstase, Andrei (CEP USM, 2024)
Outrage is a common law offense committed against the public authority, being criminalized in most of the criminal legislation of the European Union states. The object of study of this scientific approach is the offense of outrage through the prism of the elements of comparative criminal law, with particular reference to the criminal legislation of the states of the European Union. Apart from cognitive knowledge, which in fact constitutes the immediate object of the study, we also pursue the achievement of a mediated, more distant objective, through which we propose the development and improvement of criminalizations from the Romanian criminal legislation related to the crime of insult, which in fact constitutes the basis of priority assessment and which in fact form an object of comparison.
Keywords: comparative criminal law; penal punishment; outrage; infracțiunea de ultraj